Introduction to Soliton Theory: Applications to Mechanics - Munteanu, Ligia; Donescu, Stefania; SpringerLink (Online service) (Dordrecht : Springer Netherlands : Imprint: Springer, 2005)
This monograph provides the application of soliton theory to solve certain problems selected from the fields of mechanics. The work is based of the authors’ research, and on some specified, significant results existing in the literature. The present monograph is not a simple translation of its predecessor appeared in Publishing House of the Romanian Academy in 2002. Improvements outline the way in which the soliton theory is applied to solve some engineering problems. The book addresses concrete resolution methods of certain problems such as the motion of thin elastic rod, vibrations of initial deformed thin elastic rod, the coupled pendulum oscillations, dynamics of left ventricle, transient flow of blood in arteries, the subharmonic waves generation in a piezoelectric plate with Cantor-like structure, and some problems related to Tzitzeica surfaces. This comprehensive study enables the readers to make connections between the soliton physical phenomenon and some partical, engineering problems.
to Soliton Theory -- Mathematical Methods -- Some Properties of Nonlinear Equations -- Solitons and Nonlinear Equations -- Applications to Mechanics -- Statics and Dynamics of the Thin Elastic Rod -- Vibrations of Thin Elastic Rods -- The Coupled Pendulum -- Dynamics of the Left Ventricle -- The Flow of Blood in Arteries -- Intermodal Interaction of Waves -- On the Tzitzeica Surfaces and Some Related Problems.
Keywords: Mathematics; Mathematics, general